Peer-assisted learning (PAL): skills lab tutors’ experiences and motivation - Bugaj, Till Johannes; Huhn, Daniel; Herzog, Wolfgang; Krautter, Markus; Nikendei, Christoph (BMC medical education, 2019)
Peer-assisted learning (PAL) is a common teaching and learning method in medical education worldwide. In the setting of skills laboratories (skills labs), student tutors are often employed as an equivalent alternative to faculty teachers. However, to the best of our knowledge, there is a lack of qualitative studies which explore the reasons for the personal commitment of student tutors. The aim of our study was to examine how undergraduate students experienced and evaluated their roles as skills lab student tutors, what their motivation was, and whether social and cognitive congruence played a role in their teaching experiences.